Two unlinked genes for the pyruvate dehydrogenase complex in Aspergillus nidulans. - Payton, M A (1977)
The activity of the overall pyruvate dehydrogenase complex was found to be similar in extracts of Aspergillus nidulans after growth on either sucrose or acetate. Eight mutants lacking the activity of this complex were found among some 200 glycolytic mutants selected for their inability to grow on sucrose. The absence of pyruvate dehydrogenase complex activity was also confirmed for a mutant, g6 (pdhA1), isolated previously. Studies with the mutants supported the existence of two unlinked genes, pdhA and pdhB, controlling the function of the complex. In vivo and in vitro complementation between mutations at the two loci were shown by the ability of forced heterokaryons to grow on sucrose and by the restoration of overall pyruvate dehydrogenase complex activity in mixed cell-free extracts. The mutations were recessive to their wild-type alleles, and the pdhA and pdhB loci were assigned to linkage groups I and V, respectively.